1999 IEEE International Conference on Acoustics, Speech, and Signal Processing. Proceedings. ICASSP99 (Cat. No.99CH36258) 1999
DOI: 10.1109/icassp.1999.756261
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform filterbank bandwidth allocation for system modeling subband adaptive filters

Abstract: Subband adaptive filters have been used extensively in system modeling configurations to model unknown systems with large impulse responses. This paper will illustrate the advantages of a non-uniform subband adaptive filter over a uniform subband adaptive filter while giving insight to subband bandwidth allocations for system modeling configurations. By implementing small subbands which isolate the transition regions in the unknown system, while using larger subbands for other, more spectrally flat regions, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The oversampled filter bank approach can also admit services with different data rates and latency requirements by bonding sub-channels based on partioned or constituent filter banks [26].…”
Section: A Filter Bank Based Transceiversmentioning
confidence: 99%
“…The oversampled filter bank approach can also admit services with different data rates and latency requirements by bonding sub-channels based on partioned or constituent filter banks [26].…”
Section: A Filter Bank Based Transceiversmentioning
confidence: 99%
“…Results in [6] and [7] have indicated that nonuniform subband adaptive filters may give increased performance over their uniform counterparts. Nonuniform subband adaptive filters offer extra degrees of freedom over their uniform subband adaptive filters by allowing the subband filters to have independent, variable bandwidths.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, the subband decimation factors need not be equal. By allowing the decimation factors, and analysis/synthesis filters to change, the nonuniform subband adaptive filter can adaptively modify the subband bandwidths in real-time [7], [8] to best minimize the overall fullband MSE. This analysis estimates the overall fullband MSE after convergence given a particular nonuniform filterbank.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in [4] [5] has been extended in this paper by introducing a filterbank structure appropriate for efficient NDS and examining the exact sources of error in uniform SAFs. These are crucial issues, as no suitable dynamic structure has been previously suggested and if complexity is not taken into account, improvements in performance cannot be evaluated consistently.…”
Section: Introductionmentioning
confidence: 99%